Benign Brenner tumor of the ovary: two-dimensional and contrast-enhanced ultrasound features—a retrospective study from a single center - Chen, Mei; Liao, Shusheng; Cao, Yong; Mao, Meiya; Jia, Xiupeng; Zhang, Shengmin; Xu, Youfeng (Frontiers in Oncology, 2024)
Objective: Benign Brenner tumor (BBT) is a rare ovarian tumor and there are few discrete reports about its manifestation of ultrasound. This study sought to investigate the Two-Dimensional(2D) and Contrast-Enhanced Ultrasound(CEUS) features of this entity.Methods: This is a retrospective single-center study. The clinical manifestations, laboratory examination and ultrasound data of 25 female patients with BBT confirmed by pathology who underwent 2D and/or CEUS examination in Ningbo First Hospital from January 2012 to June 2023.The ultrasound findings of the patients were analyzed using the terminology of the International Organization for the Analysis of Ovarian Tumor，and were read by 2 senior sonographers and reached an agreement.Of the all 25 patients, most of them were unilateral, and only one patient were bilateral. So, 26 lesions were found. 44.0%(11/25) were in left, and 52.0%(13/25) were in right. 53.84%(14/26) were solid lesions, and 15.38%(4/26) were mixed lesions, 26.92%(7/26) were cystic lesions. Among the solid type patients, there had 42.85% (6/14) with calcification. In Laboratory examination，there were 12.0% (3/25) of the patients had high Carbohydrate antigen 125(CA-125) level, and 19.04% (4/21) of the patients had elevated Carbohydrate antigen724(CA-724) level in serum tumor marker.In hormone test,14.28% (3/21) were found to have high postmenopausal estrogen level and 14.28%(3/21) were found to have high Follicle-stimulating Hormone(FSH). One patient with complex manifestations and three with solid manifestations were examined by CEUS to observe the microcirculation perfusion of the tumor. One with solid and cystic separation was rapidly hyper enhanced and cleared, and the filling subsided faster than the uterus. The postoperative pathological diagnosis was benign Brenner tumor with mucinous cystadenoma. The other three cases were solid adnexal lesions, which showed isoenhancement on CEUS and disappeared slowly, synchronizing with the uterus. The CEUS results were considered as benign tumors, and confirmed by pathology.Conclusions: BBT can show ovarian cystic, mixed cystic and solid type, and solid echo in 2D ultrasound. Unilateral ovarian fibrosis with punctate calcification is an important feature of BBT in 2D ultrasound. However, for solid adnexal masses and mixed cystic and solid masses with unclear diagnosis, if CEUS shows isoenhancement or hyperenhancement, the possibility of BBT cannot be excluded.